Implementasi Model Project Based Learning (PJBL) dalam Materi Menyajikan Teks Persuasi Secara Tulis di Kelas VIII MTs. Pancasila Kota Bengkulu - Marlina, Reni; Kasmantoni; Friantary, Heny (Universitas Al-Qolam Malang, 2025)
The study entitled Implementation of Project Based Learning (PjBL) Model in Presenting Persuasive Text in Written Material in Class VIII MTs Pancasila Bengkulu City aims to describe the implementation of the PjBL model applied by teachers in accordance with the RPP. The subjects of this study were Indonesian language teachers in class VIII at MTs Pancasila Bengkulu City. The study used a descriptive qualitative approach with data collection techniques through interviews and observations. The results of the study showed that the implementation of project-based learning had run according to the stages. The stages of determining basic questions, designing product planning, arranging project schedules, and testing project results were carried out well. However, the stage of monitoring project development has not run optimally. Knowledge evaluation also still needs to be improved. The inhibiting factor in the implementation of this model is the limited school facilities. However, the enthusiasm of students is quite high, so that the implementation of the PjBL model continues to run effectively. In conclusion, the implementation of the Project Based Learning model in learning persuasive text in class VIII MTs Pancasila has run well according to the stages of the model and the learning plan that has been designed by the teacher.